ADOPTION OF INNOVATION IN CORN: ADOPTION DIVERSITY AND ASSOCIATED CHARCTERISTICS OF FARMERS IN GORONTALO, INDONESIA - Sirajuddin, Zulham; Rauf, Asda; Lole, Ririn (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Gorontalo Province in Indonesia is known for its corn production, yet it falls short of the national productivity average. This shortfall is attributed to the minimal use of technological advancements in corn farming. This study aims to (1) identify the components of innovation in corn farming as recommended in Good Agricultural Practice, (2) explore the diversity in adopting innovations in hybrid corn farming, and (3) examine the relationship between farmer characteristics and the adoption of innovations to enhance corn productivity. Findings indicate that several recommended innovations in corn farming have been widely adopted by farmers, with adoption influenced by demographic factors such as age and farming experience, as well as socio-economic variables including farmer participation in farmer groups and agricultural extension activities. Encouraging active adoption of innovations among farmers is thus crucial for improving corn yields.